2010
DOI: 10.1586/eci.10.26
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of calprotectin and lactoferrin as markers of inflammation in patients with inflammatory bowel disease

Abstract: Crohn's disease and ulcerative colitis have a feature in common (i.e., chronic inflammation). Their clinical management requires repeated assessments; endoscopy with histological examination remains the gold standard for detecting and quantifying intestinal inflammation. An ideal marker should be quick and easy to obtain noninvasively, and should be inexpensive and reproducible. Several laboratory tests have been studied but, to date, a disease marker is not yet available. A combination of signs and symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Fecal biomarkers, such as the neutrophil-derived calprotectin and lactoferrin, have proved useful for managing CD patients in several settings, as previously reported in two recent reviews 89,90. Both fecal calprotectin and lactoferrin significantly correlate with endoscopic and histological scores of CD activity in ileocolonic or colonic disease, but not when the disease is confined to the ileum 91,92.…”
Section: Biomarkersmentioning
confidence: 73%
“…Fecal biomarkers, such as the neutrophil-derived calprotectin and lactoferrin, have proved useful for managing CD patients in several settings, as previously reported in two recent reviews 89,90. Both fecal calprotectin and lactoferrin significantly correlate with endoscopic and histological scores of CD activity in ileocolonic or colonic disease, but not when the disease is confined to the ileum 91,92.…”
Section: Biomarkersmentioning
confidence: 73%
“…The role of FC was examined in many other gastrointestinal diseases such as inflammatory bowel disease (IBD), acute gastroenteritis, and malignancies [14]. The use of FC in CDI diagnosis was also demonstrated in a few studies; however, this marker showed restricted utility for assessing CDI severity [1115].…”
Section: Introductionmentioning
confidence: 99%
“…The use of these markers has expanded to include making initial diagnosis and differentiating between IBD and other diseases, evaluating the symptoms of active IBD to rule out flare-ups, postoperative evaluation, monitoring the response to therapy, and predicting relapse. [505152535455565758596061626364] Historically, inflammatory markers such as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were used for these indications, but have since fallen out of favor as they are generally non-specific. [65] More recently, markers of inflammation that are specific to the GI tract, such as fecal calprotectin (FC) and stool lactoferrin (SL), have been introduced.…”
Section: Resultsmentioning
confidence: 99%